Infinite photovoltaic solar arrays: Considering flux of momentum and heat transfer. (August 2020) - Glick, Andrew; Ali, Naseem; Bossuyt, Juliaan; Recktenwald, Gerald; Calaf, Marc; Cal, Raúl Bayoán
Abstract: Large scale solar farms supply an increasing amount of the worlds electricity supply. However, high operation temperatures can strongly reduce efficiency and panel lifetime, negatively affecting the levelized cost of energy. In this work, the convective heat transfer coefficient for a utility-scale solar farm is studied with combined thermal and particle-image-velocimetry measurements in a scaled wind tunnel experiment. The measurements confirm the applicability of the scaled experimental setup to study large solar arrays. Further, the velocity measurements indicate the complex flow structure within the solar array, governed by wakes directed upwards due to the orientation of the solar panels. Highlights: First experimental platform developed for scaled solar photovoltaics experiments. System-level alterations produce an increase in the heat transfer coefficient. Flow physics mechanisms are tied to the improvements and thereby explained. Models could incorporate these system-level alterations for increased accuracy.